CORAK PESANTREN TRADISIONAL DAN MODERN DALAM PERKEMBANGAN ISLAM DI SERUYAN RAYA - Robiansyah Robiansyah; Zainap Hartati (CV. Adiba Aisha Amira, 2026)
This research aims to analyze the sociological characteristics and typologies of Islamic education at the Raudlotut Tolibin Islamic Boarding School and MI Al-Mukmin (PP. Bumi Solawat Al-Mukmin) in Seruyan Raya District, Central Kalimantan. The research method employed is a qualitative approach with a library research design and documentary study. Data analysis techniques utilized content analysis through an interactive model encompassing data reduction, descriptive data presentation, and conclusion drawing. Research findings indicate that the development of Islam in Bangkal and Selunuk Villages reflects an organic model of religious moderation, characterized by the physical coexistence of houses of worship alongside symbols of the local Dayak culture. Institutionally, there is a harmonious dialectic between the salafiyah pattern, which maintains the originality of faith through the mastery of classical yellow books (kitab kuning), and the khalafiyah pattern, which is adaptive through an innovative and environment-oriented educational vision. Specifically, MI Al-Mukmin's vision successfully synchronizes the demands of flagship school standards with the preservation of local cultural activities as an effort to protect Muslim identity from the currents of globalization. The synergy of these two boarding school typologies represents an integral educational model that is most effective in addressing multi-sectoral challenges while serving as an anchor for social stability in the hinterlands of Kalimantan